Ze wspomnień o księdzu Teodorze Korczu pierwszym proboszczu w Gorzycach Wielkich - Wolniewicz, Marian (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
The beginnings (from 1936) of the history of the parish in Gorzyce Wielkie, which originated from a part of a parish in Ostrów Wielkopolski, are shown through the fascinating personality of Fr. Teodor Korcz, who became its first pastor. His interests by far exceeded traditional pastoral ministry. The text is a valuable contribution to studies on the depiction of the rural community in the religious, social, folk and even folkloristic aspects. The author of the text, Fr. Marian Wolniewicz, was a witness of Fr. Korcz’s activity, so his account can be recognized as a genuine testimony.